2013
DOI: 10.1007/s12013-013-9514-y
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Pulsed Electromagnetic Field Affects Proliferation, Tissue-Specific Gene Expression, and Cytokines Release of Human Tendon Cells

Abstract: Low frequency pulsed electromagnetic field (PEMF) has proven to be effective in the modulation of bone and cartilage tissue functional responsiveness, but its effect on tendon tissue and tendon cells (TCs) is still underinvestigated. PEMF treatment (1.5 mT, 75 Hz) was assessed on primary TCs, harvested from semitendinosus and gracilis tendons of eight patients, under different experimental conditions (4, 8, 12 h). Quantitative PCR analyses were conducted to identify the possible effect of PEMF on tendon-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 57 publications
5
80
1
1
Order By: Relevance
“…Moreover, a slight increase in cell proliferation was observed in the same experimental setting [56, 57]. The anti-inflammatory effect of PEMFs was reported also in other cell types, such as rat BMSCs, where they were able to reduce the production of IL-1β and TNFα in a pathological model [27].…”
Section: Pulsed Electromagnetic Fieldmentioning
confidence: 87%
“…Moreover, a slight increase in cell proliferation was observed in the same experimental setting [56, 57]. The anti-inflammatory effect of PEMFs was reported also in other cell types, such as rat BMSCs, where they were able to reduce the production of IL-1β and TNFα in a pathological model [27].…”
Section: Pulsed Electromagnetic Fieldmentioning
confidence: 87%
“…The choice of the collagenase doses included in this work was based on our previous in vitro studies, in which the dose inducing the collagen fiber disruption was validated in tendon explants [31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported before that MF could elicit proliferative response in various cell types [19,20]. Since no direct tumorigenic or mutagenic effect has been attributed to MF [21], it has been hypothesized that MF played the role of a tumor promoter in the presence of a primary initiator via different mechanisms, particular that involved in apoptosis [22].…”
Section: Discussionmentioning
confidence: 99%